The POP of SAA school of management 2023 - Edoardo Cravero; Jacopo Ceste; Francesco Aggeri; Ertan Akpinar (European Journal of Volunteering and Community-Based Projects)
The popupar report goes through SAA financial and non performances in order to present the institution to the general public